(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article analyzes the basic principles of financial sustainability of the enterprise. The basic methodical approaches to management of financial stability of the enterprise are determined, an overview of theoretical approaches to the definition of «financial reporting» is made, a new theoretical support of financial stability of the enterprise is summarized. Improved directions for increasing the company’s potential sustainability based on manipulating the rate of change in the indicators of available assets, their individual elements and effective economic characteristics. During the study of the systematic evaluation of financial stability, analytical indicators of the coefficient of financial autonomy or independence were proposed, organizational measures were developed for managing financial sustainability of production enterprises, the main elements of the financial policy of industrial enterprises were identified by analytical direction in order to increase the financial and economic stability of enterprises. In market conditions, financial stability serves as a pledge of survival and the basis of a stable state of the enterprise. Financial stability characterizes the state of financial resources, in which the enterprise, freely disposing of funds, can by means of their effective use ensure an uninterrupted process of production and sale of products, as well as cover the costs of expanding and updating production. The organization and management of financial sustainability is an essential aspect of the financial and economic service of the enterprise and includes a number of organizational measures that cover planning, operational management, and the creation of a flexible organizational structure for managing the entire enterprise and its divisions. Determining the boundaries of financial sustainability of enterprises refers to the most important economic problems in the market relations, as insufficient financial stability can lead to the lack of funds for enterprises to develop production, their insolvency and, eventually, to bankruptcy, and «excessive» stability will hinder development, burdening the enterprise with unnecessary stocks and reserves. The purpose of this article is to analyze and develop measures to improve the financial sustainability of enterprises. In order to achieve the intended purpose in the article the following tasks are set: to investigate the essence of financial stability of the enterprise; to study the methodology of assessing financial sustainability of the enterprise; to analyze methods of managing financial stability; to analyze the financial sustainability of enterprises; to develop organizational measures for managing financial sustainability at production enterprises.